1999
DOI: 10.1177/002215549904700303
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Subcellular Expression of Golf/Gs and Gq/G11 α-Subunits in Rat Pancreatic Endocrine Cells

Abstract: SUMMARYWe studied the cellular and subcellular localization of G ␣-subunits in pancreas by immunocytochemistry. Golf ␣ and G11 ␣ were specifically localized in islet insulin B-cells and glucagon A-cells, respectively. Gs ␣ and Gq ␣ labeling was more abundant in B-cells. The presence of Golf ␣ in B-cells was confirmed by in situ hybridization. In B-cells, Golf ␣ and Gs ␣ were found in the Golgi apparatus, plasma membrane (PM) and, remarkably, in mature and immature insulin secretory granules, mainly at the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
1
5
0
1
Order By: Relevance
“…The mediation by the Gprotein G␣ i2 -subtype is surprising in light of the current concept that GHS-R signaling is mediated primarily by the G 11 subtype (2). However, our result is consistent with the reports that G␣ i2 is expressed in ␤-cells (29,31), whereas G␣ 11 is expressed primarily in non-␤-cells in islets (32)(33)(34).…”
Section: Discussionsupporting
confidence: 93%
“…The mediation by the Gprotein G␣ i2 -subtype is surprising in light of the current concept that GHS-R signaling is mediated primarily by the G 11 subtype (2). However, our result is consistent with the reports that G␣ i2 is expressed in ␤-cells (29,31), whereas G␣ 11 is expressed primarily in non-␤-cells in islets (32)(33)(34).…”
Section: Discussionsupporting
confidence: 93%
“…We also investigated the possible role of G␣olf on insulin status, using the mouse secreting ␤TC-3 cell line in culture, because we found that G␣olf was present in insulin secretory granules of pancreatic ␤-cells (2). Several studies by others and us (17,21,28) demonstrated that all of the membrane-bound ACI-VIII isoforms are present in ␤-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we identified G␣olf in pancreatic ␤-cells by in situ hybridization, immunocytochemistry, and electron microscopy (2). In Langerhans islets, G␣olf is located inside the insulin-secretory granules and ␤-cell plasma membrane, suggesting that it is involved in granule migration, processing, and exocytosis.…”
mentioning
confidence: 99%
“…Dans l'espèce humaine, les tumeur de la granulosa synthétisent et secrètent de l'inhibine. Matzuk a donc proposé une résistance a cette hormone au sein de la tumeur [107]. La protéine p120, suspectée d'être un élément important dans la transduction du signal de l'inhibine, est sous-exprimée ou absente des les TJG par rapport aux tumeurs épithéliales et à l'ovaire normal [62].…”
Section: Inhibine Et Activineunclassified